Training on Milkfish Processing for the Community Seumadu Island, Lhokseumawe - Anismar Anismar; Muhammad Ali; Subhani Subhani (Universitas Teuku Umar, 2022)
Milkfish Processing Training for the Seumadu Island Community, Batuphat Barat Village, Muara Satu District, Lhokseumawe City is important to carry out, because nowdays Lhokseumawe - Aceh, is experiencing the Covid-19 pandemic which affects almost all sectors of the community's economy, including the tourism sector, so that it can boost the community's economy, especially the family economy, because milkfish has been a side sector for the people on Seumadu Island in addition to the tourism sector. There is also a method that is designed in this presto milkfish processing training to involve two groups of people who live in the tourism area of Seumadu Island, including: a group of housewives, and a youth group of Karang Taruna. Then these activities are also trained by experts in their fields who have experience in conducting fish processing training outside Aceh. Among the various types of fish, milkfish is one of the fish that is easy to find and has a lot of nutrition, because it contains many spines so that it is less attractive to the public. Then, milkfish also smells of earth, so many people do not like it. The smell of earth in fish can be caused by the presence of geosmin compounds produced by the fungus Actinomycetes and blue algae Oscillatoria tenus. This often occurs in ponds that are shallow and located far from the sea (land ponds), with this training, it can make milkfish taste more delicious and odorless, so that it can be liked by the general public.